Bearing capacity envelopes of wide-shallow bucket foundations in sand under combined horizontal and moment loading - Run Liu; Rui Zhou; Xiang-chuan Meng; Yu Wang (Ocean Engineering, 2026)

Intracellular imaging and therapeutic application of liver fibrosis via a microRNA-on self-stacking amplification circuit - Xiao-Meng Sun; Yin-Xiang Chen; Lin-Ru Xu; Rui Bai; Li-Zeng Zhu; Gaoxiang Ma; Lian-Wen Qi; Yu Gu; Qun Liu (Analytica Chimica Acta, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Data-driven discovery of high-performance surface passivators for efficient and stable perovskite solar cells - Feiyi Zhou; Zeyu Wang; Shangshang Zhao; Xu Zhang; Qingyue Guo; Runze Dai; Fanxiang Meng; Huajie Lyu; Jun Wan; Yi Dong; Zhe Jin; Shanqing Yu; et al. (Chemical Engineering Journal, 2026)

Effects of in-situ stress direction and orientation of structure planes on rockburst generation in deep tunnels: 56 case studies - Ben-Guo He; Xiang-Rui Meng; Bo Lin; Hong-Pu Li (Tunnelling and Underground Space Technology, 2026)

Alleviating effects and mechanism of Lacticaseibacillus paracasei BHP06 on the allergic reactions induced by ovalbumin - Xiang-Ge Xin; Yue Meng; Jun Meng; Jun Xi; Chang-He Ding; Rui-Han Ge; Yu-Tong Bai; Ming-He Li (Food Bioscience, 2026)

Wave-absorbing grouting for mitigating rockbursts triggered by multi dynamic disturbances in deep tunnels - Heng-Yuan Zhang; Ben-Guo He; Xiang-Rui Meng; Jia-Hua Guan; Hua-Wei Xu (Tunnelling and Underground Space Technology, 2026)

Mechanism of Chain Rockbursts in Deep Excavations Triggered by Dynamic Disturbance: Insights from Stress Path Controlled Failure - Biao Wang; Ben-Guo He; Xiang-Rui Meng; Hong-Pu Li; Zhao-Tong Jin (Rock Mechanics and Rock Engineering, 2026)

Expression of Beta vulgaris betaine aldehyde dehydrogenase 1 (BvBADH1) confers salt tolerance in tobacco (Nicotiana benthamiana) - Ming Wei; Xiang-Yu Chen; Meng-Li Li; Hao Li; Xin-Rui Wu; Guo-Qiang Wu (Physiology and Molecular Biology of Plants, 2026)

Bioinspired mortise-tenon interlocking HKUST-1/CuOH micro-nano architectures on stainless steel mesh for oil-water separation membranes - Xiang Li; Ping Zhang; Rui Wang; Meng Zhu; Xiaobo Gong; Yucheng Liu (Environmental Research, 2025)

Correction: Combining network Pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

Combining network pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

Fossil involucres and a nutlet of Ostrya (Betulaceae) from the upper Eocene of Shaanxi and their biogeographic implications - Jiao Huang; Hui Jia; Rui-Feng Yan; Xiang-Ning Meng; Zhuo-Chen Han; Tian-Qi Dong; Jian Pan; Cheng Quan (Palaeoworld, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Ga- and Ge-bearing minerals and trace element-rich magnetite in the Makeng skarn Fe polymetallic deposit, Eastern China - Xiang-Xue Weng; Yu-Miao Meng; Xiao-Wen Huang; Lin-Bo Shang; Rui-Zhong Hu; Xian-Wu Bi (Journal of Asian Earth Sciences, 2025)

Time-Delayed Rockbursts Induced by Dynamic Disturbances: 793 Cases in Deep Tunnels - Ben-Guo He; Heng-Yuan Zhang; Xia-Ting Feng; Xiang-Rui Meng (Rock Mechanics and Rock Engineering, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

Axial chain rockbursts in deep tunnels excavated via drilling and blasting - Hong-Pu Li; Ben-Guo He; Xiang-Rui Meng; Shengcun Yan; Tao Chen (Tunnelling and Underground Space Technology, 2025)

A magnetic nanoreactor with microenvironment regulation capability for targeted and enhanced tumor chemodynamic therapy - Xia-Nan Li; Qin-Ying Tang; Meng-Cheng Tang; Hai-Rui Deng; Kang Hu; Ling-Feng Pan; Shi-Bo Wang; Bin Li; Xiang-Dong Kong (Chemical Engineering Journal, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Enhanced regeneration of large segmental bone defects via hierarchically structured bioactive scaffolds - Mo-Han Wang; Shao-Meng Wen; Yun-Hong Cong; Huai-Ling Gao; Xian-Yu Zheng; Zi-Xiang Han; Run Wang; Rui Xu; Lu Yang; Wen-Jing Li; Zhao Pan; Jia-Cai He; et al. (Chemical Engineering Journal, 2025)

U-shaped relationship between environmental regulation and the digital transformation of the Chinese coal industry: Mechanism and moderating effects - Pu-hao Guo; Xiang-qian Wang; Xiang-rui Meng (Journal of Environmental Management, 2025)

Travel time calculation of seismic waves on complex surfaces using the group marching method - Ping Zhang; Fan-chang Meng; Xiao-hang Zhao; Jian-hui Deng; Rui Chen; Hong-yong Ren; Xiang-yu Tan; Gong-min Chen (Applied Geophysics, 2024)

Recovery of low-concentration waste acid by electrodialysis: Modeling and validation - Feng-rui Li; Yu-xiang Jia; Meng Wang (Journal of Cleaner Production, 2024)

Assessment of brittle failure in deep tunnels via true triaxial compression - Ben-Guo He; Hong-Pu Li; Xiang-Rui Meng; Si-Yuan Dou; Shengcun Yan; Tao Chen (Tunnelling and Underground Space Technology, 2024)

An “off-on-enhanced on” electrochemiluminescence biosensor based on resonance energy transfer and surface plasmon coupled 3D DNA walker for ultra-sensitive detection of microRNA-21 - Meng-Li Li; Ming-Yu Zhong; Jia Zhang; Yi-Jia Zhang; Yu-Qi Zhang; Yan Liu; Xiang-Kai Li; Shu-Tian Gan; Gong-Rui Meng; Li Mi; Yong-Hong Hu; Fang Zhang; et al. (Analytica Chimica Acta, 2024)

Two new monoterpene esters from Illigera paviflora Dunn roots - Meng-Yuan Jiang; Xiao-Yun Pu; Wen-Ting Li; Juan Liu; Xiao-Li Zeng; Hong-Rui Li; Xi-Shan Bai; Lin Hu; Xiang-Zhong Huang (Natural Product Research, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Scrub-vegetation cover impact on soil water migration and temperature change during freeze–thaw events in sandy desert soils of northwest China - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li; Ruiting Jia (CATENA, 2024)

Impacts of re-vegetation on soil water dynamics in a semiarid region of Northwest China - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li (Science of The Total Environment, 2024)

Vegetation-cover control of between-site soil temperature evolution in a sandy desertland - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li; Yalu Han; Shuang Feng; Lin Miao; Chen Liu (Science of The Total Environment, 2024)

Seasonal variations of microplastics in surface water and sediment in an inland river drinking water source in southern China - Wenyu Zhao; Jing Li; Mengyue Liu; Rui Wang; Boxuan Zhang; Xiang-Zhou Meng; Shengwei Zhang (Science of The Total Environment, 2024)

Inverse kinetic isotope effect of proton and deuteron permeation through pyridinic N-doped graphene - Jingwen Ba; Jinfan Chen; Renjin Xiong; Jingsong Xu; Haibo Li; Xiayan Yan; Cheng Qin; Rui Li; Qifa Pan; Xinxin Tan; Tao Tang; Xin Xiang; et al. (Chemical Engineering Journal, 2024)

Estimating the complete in-situ stress tensor along deep tunnels with frequent rockbursts near a steep valley - Ben-Guo He; Hong-Pu Li; Xia-Ting Feng; Xiang-Rui Meng (Bulletin of Engineering Geology and the Environment, 2024)

Integration of deep learning algorithms with a Bayesian method for improved characterization of tropical deforestation frontiers using Sentinel-1 SAR imagery - Rui Sun; Feng Zhao; Chengquan Huang; Huabing Huang; Zhong Lu; Ping Zhao; Xiang Ni; Ran Meng (Remote Sensing of Environment, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Rethinking personal carbon trading (PCT) mechanism: A comprehensive review - Yun-En Tang; Ru Fan; Ang-Zu Cai; Le-Yi Wang; Rui-Min Lin; Xiang-Zhou Meng; Ling Chen; Ru Guo (Journal of Environmental Management, 2023)

Revealing the solid-solution interface interference behaviors between Cu2+ and As(III) via partial peak area analysis of simulations and experiments - Bo Liang; Xiang-Yu Xiao; Zong-Yin Song; Yong-Yu Li; Xin Cai; Rui-Ze Xia; Shi-Hua Chen; Meng Yang; Pei-Hua Li; Chu-Hong Lin; Xing-Jiu Huang (Analytica Chimica Acta, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Effects of dietary protein concentration on growth and anti-oxidant capacity of coho salmon Oncorhynchus kisutch (Walbaum, 1792) alevins - Cong-mei Xu; Hai-rui Yu; Qin Zhang; Ling-yao Li; Jing-jing Fan; Meng-jie Guo; Fang-hui Li; Xiang-yi Qiu; Ling-ling Shan (Aquaculture International, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Secondary metabolites isolated from Agrimonia pilosa Ledeb. - Hong-Rui Li; Yu-Kui Li; Jian Xiao; Cui Yang; Meng-Yuan Jiang; Kai Tian; Wei Wang; Yan-Hong Li; Xiang-Zhong Huang (Natural Product Research, 2022)

Establishment of an immortalized cell line derived from the pupal ovary of Mythimna separata (Lepidoptera: Noctuidae) and identification of the cell source - Yan Tong; Lu-Qiang Cheng; Xuan Li; Xu-Peng Yu; Rui-Hao Shu; Ji-Hong Zhang; Qian Meng; Qi-Lian Qin; Kai Tang; Jian-Xiang Xu; Huan Zhang (Cell and Tissue Research, 2021)

Clarification of the etiology of peach bacteria leaf shot hole caused by Pantoea spp. in Henan Province, China, based on morphological characteristics and multi-locus sequences analysis - Rui Zang; Lu-lu Song; Chao Xu; Xin-ming Yin; Zhan-xiang Qiao; Yue-hua Geng; Meng Zhang (European Journal of Plant Pathology, 2021)

Development of 19 novel microsatellite markers of lily-of-the-valley (Convallaria, Asparagaceae) from transcriptome sequencing - Qi-Xiang Lu; Jing Gao; Jun-Jie Wu; Xuan Zhou; Xue Wu; Meng-Di Li; Yu-Kun Wei; Rui-Hong Wang; Zhe-Chen Qi; Pan Li (Molecular Biology Reports, 2020)

Appropriate Dynamically-Reinforced Supporting Time Determination in Relation to the Time Effect of Stress Field Evolution: A Case Study on the Deep Soft-Rock Roadway in China - Li Cong; Ying-ming Li; Xiang-rui Meng; Chun-liang Dong; Guang-ming Zhao; Rui Peng; Ji-cheng Xu (Geotechnical and Geological Engineering, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Similar simulation device for unloading effect of deep roadway excavation and its application - Chun-liang Dong; Guang-ming Zhao; Xiao-yu Lu; Xiang-rui Meng; Ying-ming Li; Xiang Cheng (Journal of Mountain Science, 2018)

ABA pretreatment enhances the chilling tolerance of a chilling-sensitive rice cultivar - Xiang Hongtao; Wang Tongtong; Zheng Dianfeng; Wang Lizhi; Feng Yanjiang; Luo Yu; Li Rui; Li Zhongjie; Meng Ying; Li Wan; Wang Lianmin; Yang Chunjie (Brazilian Journal of Botany, 2017)

Genome editing in potato plants by agrobacterium-mediated transient expression of transcription activator-like effector nucleases - Jin Ma; Heng Xiang; Danielle J. Donnelly; Fan-Rui Meng; Huimin Xu; Dion Durnford; Xiu-Qing Li (Plant Biotechnology Reports, 2017)

Systematic Review by Multivariate Meta-analyses on the Possible Role of Tumor Necrosis Factor-α Gene Polymorphisms in Association with Ischemic Stroke - Yu-Ming Niu; Hong Weng; Chao Zhang; Rui-Xia Yuan; Jin-Zhu Yan; Xiang-Yu Meng; Jie Luo (NeuroMolecular Medicine, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

Tropomyosin-related kinase B promotes distant metastasis of colorectal cancer through protein kinase B-mediated anoikis suppression and correlates with poor prognosis - Meng Fan; Jianyong Sun; Wei Wang; Jing Fan; Lei Wang; Xiang Zhang; Angang Yang; Weizhong Wang; Rui Zhang; Jipeng Li (Apoptosis, 2014)

Isolation and characterization of microsatellite markers from Lagerstroemia caudata (Lythraceae) and cross-amplification in other related species - Ming Cai; Rui Meng; Hui-Tang Pan; Yi-Ke Gao; Ming Sun; Ping Song; Xue-Feng Wang; Qi-Xiang Zhang (Conservation Genetics Resources, 2010)

Identification of a novel rice bZIP-type transcription factor gene,OsbZIP1, involved in response to infection ofMagnaporthe grisea - Xiang-Bing Meng; Wen-Sheng Zhao; Rui-Ming Lin; Min Wang; You-Liang Peng (Plant Molecular Biology Reporter, 2005)